2018
DOI: 10.29303/jp.v8i2.114
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN PAKAN KEONG MAS TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP LOBSTER PASIR (Panulirus homarus)

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian pakan keong mas terhadap pertumbuhan dan kelangsungan lobster pasir (Panulirus homarus). Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan perlakuan; Perlakuan P1 (100 % ikan rucah sebagai control), P2 (50 % ikan rucah + 50 % keong mas segar), P3 (50 % ikan rucah + 50 % keong mas olahan), P4 (100 % keong mas segar), P5 (100 % keong mas olahan). Data yang diperoleh dianalisa menggunakan analysis of variance (ANOVA) dengan taraf nyata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
2
4
1
2
Order By: Relevance
“…This is in accordance with the statement of Anggraini et if the taste of the feed is in accordance with the lobster's desire, the feed will be consumed, on the contrary if the taste and aroma of the feed are not suitable, the feed will be left or not consumed [3]. Feed conversion ratio is the amount of feed given during maintenance to bolster lobster weight gain [3]. The result showed that formulated diets with different protein sources did not significantly affect the feed conversion ratio.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This is in accordance with the statement of Anggraini et if the taste of the feed is in accordance with the lobster's desire, the feed will be consumed, on the contrary if the taste and aroma of the feed are not suitable, the feed will be left or not consumed [3]. Feed conversion ratio is the amount of feed given during maintenance to bolster lobster weight gain [3]. The result showed that formulated diets with different protein sources did not significantly affect the feed conversion ratio.…”
Section: Resultssupporting
confidence: 89%
“…The high feed consumption in the control treatment (T0) was because trash fish had an odor that was favored by lobsters, thereby increasing the lobster's response to feed. This is in accordance with the statement of Anggraini et if the taste of the feed is in accordance with the lobster's desire, the feed will be consumed, on the contrary if the taste and aroma of the feed are not suitable, the feed will be left or not consumed [3]. Feed conversion ratio is the amount of feed given during maintenance to bolster lobster weight gain [3].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results showed that different proteins did not affect feed efficiency (p>0.05). Feed efficiency in this study range from of 38.92-42.50%, these results was higher than research Anggraini et al,2018 where the value of feed efficiency range from 15,27-27,83 % [18]. The highest feed efficiency value at 50% protein treatment (P3: 42.50%), the increase in efficiency value indicates that the feed consumed could be utilized properly, so that the protein was remodeled to meet the energy needs and the rest for growth.…”
Section: Feed Efficiencycontrasting
confidence: 57%
“…Makanan keong mas dan sayuran yang disajikan dalam kondisi mentah atau setengah matang (undercooked) digemari oleh masyarakat di negara tertentu. Kandungan protein keong mas sebesar 16-50% menjadikan keong mas sebagai bahan pangan sumber protein alternatif (Anggraini et al, 2018). Parasit nematoda zoonotik Angiostrongylus cantonensis adalah cacing parasitik yang dapat menginfeksi keong mas.…”
Section: Pendahuluanunclassified